Counselling services for gifted students in Malaysia: A qualitative exploration - Yazid Abu Bakar, Abu; Zakaria, Zulkarnin (International Journal of Engineering and Technology, 2018)
This research is conducted to study in detail issues regarding the perception and experience of local gifted and talented students towards guidance and counselling service in their school environment. Research sample includes 30 students from the first and second cohort in a ‘lab’ school that provides a special-need education programme for the gifted and talented students. This qualitative study combines focus group and in-depth interview as data collection method, and the data is analysed in detail using NVivo version 10.0.  Findings show that the issues affecting the local gifted and talented students are related to their career and academic pathway as well as psychosocial being. Their uncertainties have encouraged them to seek for guidance and counselling services. Findings also indicate that the students’ perception and experience on the guidance and counselling service in general are made of both positive and negative reactions.  The overall findings are discussed in the context of suggestions for best practices and differentiated school counselling services that cater towards local gifted and talented student’s population.